Identification of 17 HrpX-regulated proteins including two novel type III effectors, XOC_3956 and XOC_1550, in Xanthomonas oryzae pv. oryzicola. - Xiao-bo Xue; Li-fang Zou; Wen-xiu Ma; Zhi-yang Liu; Gong-you Chen (PLoS ONE)
The function of some hypothetical proteins, possibly regulated by key hrp regulators, in the pathogenicity of phytopathogenic bacteria remains largely unknown. In the present study, in silicon microarray data demonstrated that the expression of 17 HrpX-regulated protein (Xrp) genes of X. oryzae pv. oryzicola (Xoc), which causes bacterial leaf streak in rice, were either positively or negatively regulated by HrpX or/and HrpG. Bioinformatics analysis demonstrated that five Xrps possess a putative type III secretion (T3S) signal in the first 50 N-terminal amino acids, six xrp genes contain a PIP-box-like sequence (TTCGB-NX-TTCGB, 9 ≤ X ≤ 25) in the promoter regions, and two Xrps have both motifs. Twelve Xrps are widely conserved in Xanthomonas spp., whereas four are specific for X. oryzae (Xrp6) or Xoc (Xrp8, Xrp14 and Xrp17). In addition to the regulation by HrpG/HrpX, some of the 17 genes were also modulated by another hrp regulator HrpD6. Mutagenesis of these 17 genes indicated that five Xrps (Xrp1, Xrp2, Xrp5, Xrp8 and Xrp14) were required for full virulence and bacterial growth in planta. Immunoblotting assays and fusion with N-terminally truncated AvrXa10 indicated that Xrp3 and Xrp5 were secreted and translocated into rice cells through the type-III secretion system (T3S), suggesting they are novel T3S effectors. Our results suggest that Xoc exploits an orchestra of proteins that are regulated by HrpG, HrpX and HrpD6, and these proteins facilitate both infection and metabolism.